Inquiry of deaths under the Malaysian Criminal Procedure Code - Kamarudin, Abdul Rani (LexisNexis Malaysia Sdn Bhd, 2009)
This paper deals with any sudden death or unnatural death or death by violence or of any death under suspicious circumstances, or of the body of any person being found dead without its being known how that person came by death. It discusses among others, on the requirement to inform the relevant autorithies especially the police, the manner of investigation to be conducted and whether a post-mortem of the deceased is required. It also looks at the nature of the inquiry, the powers given to the magistrates in ascertaining the cause of death, the rules of evidence and the procedures involved. The powers of the public prosecutor and the role of the pathologist in relation to the death of the person are also discussed.